2022
DOI: 10.1186/s13244-022-01264-x
|View full text |Cite
|
Sign up to set email alerts
|

T2-weighted MRI-based radiomics for discriminating between benign and borderline epithelial ovarian tumors: a multicenter study

Abstract: Background Preoperative differentiation between benign and borderline epithelial ovarian tumors (EOTs) is challenging and can significantly impact clinical decision making. The purpose was to investigate whether radiomics based on T2-weighted MRI can discriminate between benign and borderline EOTs preoperatively. Methods A total of 417 patients (309, 78, and 30 samples in the training and internal and external validation sets) with pathologically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In conclusion, Wei et al 8 demonstrated the potential of DL and radiomics‐based models for predicting PM in EOC patients from T2‐weighted MR images. This model achieved high accuracy and showed good generalizability and robustness across different cohorts, highlighting its potential clinical utility 8 .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In conclusion, Wei et al 8 demonstrated the potential of DL and radiomics‐based models for predicting PM in EOC patients from T2‐weighted MR images. This model achieved high accuracy and showed good generalizability and robustness across different cohorts, highlighting its potential clinical utility 8 .…”
mentioning
confidence: 90%
“…Artificial intelligence (AI), particularly deep learning (DL) and radiomics, has shown promise in oncology and radiology research. However, existing MRI‐based radiomics models for predicting PM in EOC patients have limitations, including small sample sizes and a lack of external validation 4–7 . Additionally, it is unclear whether AI‐assisted models can help radiologists improve their diagnostic performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these aforementioned studies did not employ the DL method, which has been shown to accurately predict PM of gastric cancer 18 . T 2 ‐weighted (T2W) imaging based radiomics models have been demonstrated to identify benign, borderline, and malignant EOC, which is helpful to reduce MRI scan time and examination cost 19,20 . However, the use of AI models based on only a single MRI sequence in predicting PM remains unclear.…”
mentioning
confidence: 99%
“…18 T 2 -weighted (T2W) imaging based radiomics models have been demonstrated to identify benign, borderline, and malignant EOC, which is helpful to reduce MRI scan time and examination cost. 19,20 However, the use of AI models based on only a single MRI sequence in predicting PM remains unclear. Moreover, whether an AI-assisted model can help radiologists improve performance in diagnosing the PM status of EOC patients is still vague.…”
mentioning
confidence: 99%